Formal and semantic characterization of joker words - Kryzan-Stanojević, Barbara (Array, 2008)
In the past ten years or so a group of words with a specific semantic profile has appeared in Croatian. In my research I have referred to them as jokers. They are characterized by schematicity and generality, which means that they can take on various functions in a sentence. Jokers include internationalisms such as super, ekstra, as well as more usual Croatian words such as guba (‘ leprosy’ ), zakon (‘ law’ ), legenda (‘ legend’ ). Their usage as jokers is related to a specific context.The research is based on language material taken from the Croatian National Corpus and Croatian Internet forums.